Case Report: Two Rare Cases of Complete Metabolic Response to Crizotinib in Patients With Rearranged ROS1 and ALK Metastatic Non-small Lung Cancer - Amrane, Karim; Campedel, Luca; Le Meur, Coline; Abgral, Ronan; Kharroubi, Dris; Cadranel, Jacques (Frontiers in Medicine, 2021)
Crizotinib is a tyrosine kinase inhibitor (TKI) indicated in first-line treatment of rearranged c-ros oncogene 1 (ROS1) and anaplastic lymphoma kinase (ALK) metastatic non-small-cell lung cancer (NSCLC). However, the common response reported after treatment is partial and few complete responses have been reported in PROFILE studies with computed tomography (CT) evaluation. To date, only one case report of complete metabolic response on 2-deoxy-2-[18F] fluoro-D-glucose positron emission tomography-computed tomography (18F-FDG-PET/CT) was published, reporting on a patient with ROS1 rearranged NSCLC. We highlighted the 18F-FDG-PET/CT useful approach for therapeutic assessment of TKI in metastatic mutated NSCLC reporting two complete metabolic responses in patients treated with crizotinib for a rearranged ROS1 and a metastatic ALK NSCLC.